An Initial Discussion of the Persistence and Movement of Water within Fractured Massifs, Case of Drainage Galleries in the Landslide - Gutiérrez, Rubén Esaú Mogrovejo (2025)
In the last 30 to 50 years, the planet has been accumulating and experiencing changes in the regional water cycle. This variation makes us all, especially in the Andes Mountain range, ask ourselves what is the current state of the persistence and movement of water from a regional to a local approach. We all know that nature is highly complex, even more so when we want to understand the elements that constitute one or more geological masses that make up, for example, a landslide. The physical stability of these is very important for civil works operations, so it is important to understand today more than before not only their properties but also the interaction with the flow of water over time. We invest high costs in indirect investigations and even more so in direct ones, with the desire to know that vertical column of the materials or natural aggregates present in these geological masses, not only understanding it is necessary, but also monitoring over time is essential with the support of hydraulic instrumentation. Given these climatic changes, the central zone of Peru is not immune to an increase in the average rainfall rates that converge in the investigated area, but now we must not only create predictive scenarios, but also expand the expectations that we used to have in the initial monitoring, adding models with high performance in modeling the flow in domains of fractured rocks. The initial results suggest an RMSE below 5%, which is an acceptable value for this initial discussion, which has allowed us to validate the filtration flows that were obtained with a range of 7 m3/hr to 18m3/hr, comparing them with the flows measured during the construction of these galleries in fractured rocks.